Peran Moderasi Kondisi Leverage terhadap Hubungan Kompensasi CEO dengan Manajemen Laba: Studi pada perusahaan Manufaktur yang terdaftar di BEI - Elizabeth Jessica; Vania Nanda Djaja; Yulius Jogi Christiawan (Business Accounting Review, 2021)
The connection between CEO compensation and earnings management has long become the object of research, ever since a study by Healy in 1985. Generally, the study on earnings management would use agency theory. Still, this study applies prospect theory which serves to explain the behavior of people or organizations when making decisions in a high-risk, uncertain situation. An organization suffering from loss will attempt to take risk, while an organization enjoying a gain will be averse to risk. A company with high leverage is in an unfavorable position compared to one with low leverage. Leverage describes a company’s debt situation. The more debt there is, the more obligations the company must fulfill, such as profit numbers. It is then presumed to be the cause for CEO to start managing earnings. This study aimed to prove if leverage condition also influences the relation between CEO compensation and earnings management.The study was done on 176 manufacturing companies listed in Indonesia Stock Exchange (IDX) in 2019 and 2020. The data analysis technique utilized panel data regression with the program Gretl. This study prove that the more compensation a CEO receives, the less inclined they are to do earnings management. However, in companies with high leverage, this correlation weakens, meaning CEOs would be more willing to manage earnings. The results of this study are expected to help shareholders in deciding CEO compensation when in a high-leverage condition.